Legume Plant Peptides as Sources of Novel Antimicrobial Molecules Against Human Pathogens - Lima, Rui M.; Rathod, Balaji Baburao; Tiricz, Hilda; Howan, Dian H. O.; Al Bouni, Mohamad Anas; Jenei, Sándor; Tímár, Edit; Endre, Gabriella; Tóth, Gábor K.; Kondorosi, Éva (Frontiers in Molecular Biosciences, 2022)
Plants have evolved large numbers of antimicrobial peptides against microbial infections. Legume plants from the inverted repeat lacking clade (IRLC) have evolved a unique gene family encoding nodule-specific cysteine-rich (NCR) peptides acting in the symbiotic cells of root nodules, where they convert their bacterial endosymbionts into uncultivable, polyploid nitrogen-fixing cells. NCRs are usually 30-50 amino acid long peptides having a characteristic pattern of 4 or 6 cysteines and highly divergent amino acid composition. While the function of NCRs is largely unknown, antimicrobial activity has been demonstrated for a few cationic Medicago truncatula NCR peptides against bacterial and fungal pathogens. The advantages of these plant peptides are their broad antimicrobial spectrum, fast killing modes of actions, multiple bacterial targets, and low propensity to develop resistance to them and no or low cytotoxicity to human cells. In the IRLC legumes, the number of NCR genes varies from a few to several hundred and it is possible that altogether hundreds of thousands of different NCR peptides exist. Due to the need for new antimicrobial agents, we investigated the antimicrobial potential of 104 synthetic NCR peptides from M. truncatula, M. sativa, Pisum sativum, Galega orientalis and Cicer arietinum against eight human pathogens, including ESKAPE bacteria. 50 NCRs showed antimicrobial activity with differences in antimicrobial spectrum and effectivity. The most active peptides eliminated bacteria at concentrations from 0.8 to 3.1 M. High isoelectric point and positive net charge were important but not the only determinants of their antimicrobial activity. Testing the activity of shorter peptide derivatives against Acinetobacter baumannii and Candida albicans led to identification of regions responsible for the antimicrobial activity and provided insight into their potential modes of action. This work offers highly potent lead molecules without hemolytic activity on human blood cells for novel antimicrobial drugs to fight against pathogens.